Comparison Of Downside Beta In Shariah-Compliant And Conventional Stocks In Malaysia - Assan Jeng (Universiti Sains Islam Malaysia, 2024)
Generally, business risks are categorized as either systematic risks or unsystematic risks. Systematic risks or beta are considered as risks that have a general impact on all securities while unsystematic risk is an intrinsic, security specific risk. The study critically studied the characteristics of downside beta for listed companies in Malaysia. The process involves a random selection of 50 Shariah-compliant and 50 conventional stock returns, analysed from January 2015 to January 2020. Firstly, the study tabled the stock returns of the market benchmark, Financial Times Stock Exchange Bursa Malaysia Kuala Lumpur Composite Index (FBM KLCI) and both Shariah-compliant and conventional stocks portfolios. The downside beta is then computed using three methods: Historical Volatility (HV), Exponentially Weighted Moving Average (EWMA) and GARCH (1,1). While analysis of the Shariah-compliant and conventional portfolio as an index can indicate statistically significant difference in their downside beta values, the randomly selected 50 portfolio stocks in this research indicated no statistically significant difference between the two. Furthermore, the Sortino ration is used to determine the beta to return performance between the two portfolios. The Sortino ratio results indicates Shariah-compliant businesses outperforms their conventional counterparts. As such, there is higher appeal for investors to adopt an Islamic business framework, provided due diligence in anchored on downside beta an d reward analysis.